SAGO FOREST ECOTOURISM POTENTIAL IN NEGERI RUTONG SOUTH LEITIMUR DISTRICT - Jeane Talakua; Rukoyah (Media Inovasi Pendidikan dan Publikasi, 2023)
The sago forest ecotourism program in Negeri Rutong has developed into a form of tourism that can conserve nature and empower the community. Sago forest ecotourism in Negeri Rutong is one of the more specific forms of ecotourism and as a tool to realize sustainable tourism development, where the village government / Negeri Rutong and local communities have control over development and management so that many benefits both economically, socio-culturally, and benefits to the conservation of the natural environment. Sago forest ecotourism in Negeri Rutong finds its significance as a protection tool against environmental, economic, social and cultural impacts arising from tourism development. In terms of the environment, the development of sago forest ecotourism provides income for conservation areas and is also able to reduce negative impacts on protected natural resources. If explored carefully, sago has multi-functions and multipurpose. So that the people of Rutong with their local knowledge and sago tradition fully participate in supporting government policies to manage and preserve sago sustainably.